Proust and the Overcoming of Realism: The stained glass of Combray’s church (Castilla. Estudios de Literatura, 2018)
The present article pursues to explore, by making a detailed textual analysis, some of the recurrenttopics of the Combray symbolic universe, where Proust condenses his aesthetic and epistemological conceptionof the world. Particularly, the stained glass of Saint-Hilaire’s church and its description in this first chapter are alsorepresentative of the proustian literary strategies, which entail the overcome of the classic realism in favor of ametaliterary symbolism. The proposed analysis, then, aims to elucidate how those architectural symbols work inthe literary construction that the Recherche is.
Keywords: Proust; Combray; church; stained glass; realism; simbolism